Incidencia del endeudamiento en la liquidez de la “exportadora Bana Sur S.A” durante los períodos 2021 – 2022. - Chillogalli Chillogalli, Xiomara Maribel; Vera Sivisapa, Dayana Julissa (Machala : Universidad Técnica de Machala, 2023)
Currently, financial analysis is of great importance in the business world because it allows knowing the financial health of an organization in terms of its solvency, and also provides relevant information for making decisions about financing, investments, budget and growth strategies. For this reason, this case analysis addresses the impact of indebtedness on the liquidity of Exportadora Bana Sur S. A.”, during the periods 2021 - 2022 with the main objective of evaluating the impact of indebtedness on the liquidity of "Exportadora Bana Sur S. A.", through the application of financial ratios to the Financial Statements for the periods 2021-2022, extracted from the Superintendency of Securities and Insurance. An exhaustive analysis of the financial statements was carried out through vertical analysis and then applying financial indicators of liquidity, indebtedness and profitability to determine the company's autonomy, optimization of resources and compliance with short-term obligations. The research has a non-experimental design and is descriptive and will be based on the positivist paradigm with quantitative approach because it is essential to apply financial formulas to reach the results and qualitative approach to expose the explanations of the occurrence of the phenomena studied. The result of this research reflects that the company has had difficulties in obtaining liquidity due to the increase of short-term debts and the unfavorable increase and decrease of certain current asset accounts, in addition to its high cost of production.
En la actualidad el análisis financiero reviste una gran importancia en el ámbito empresarial debido a que permite conocer la salud financiera de una organización en función a su solvencia, y además proporciona información relevante para la toma de decisiones acerca de financiamiento, inversiones, presupuesto y estrategias de crecimiento. Motivo por el cual el presente análisis de caso aborda la incidencia del endeudamiento en la liquidez de la “EXPORTADORA BANA SUR S.A” durante los periodos 2021 – 2022 con el objetivo principal de evaluar la incidencia que tiene el endeudamiento en la liquidez de la “Exportadora Bana Sur S. A”, mediante la aplicación de razones financieras a los Estados Financieros de los periodos 2021-2022, extraídos de la Superintendencia de Compañías Valores y Seguros. Se realizó un análisis exhaustivo de los Estados financieros a través del análisis vertical y posteriormente aplicando indicadores financieros de liquidez, endeudamiento y rentabilidad para determinar la autonomía de la empresa, optimización de recursos y el cumplimiento de obligaciones a corto plazo. La investigación tiene un diseño no experimental y es de tipo descriptivo y además se basará en el paradigma positivista con enfoque cuantitativo porque es imprescindible aplicar fórmulas financieras para llegar a los resultados para exponer las explicaciones del suceso de los fenómenos estudiados. El resultado de esta investigación refleja que la empresa ha tenido dificultades para obtener liquidez por el incremento de las deudas a corto plazo y por el incremento y disminución desfavorables de ciertas cuentas del activo corriente, además de su alto costo en la producción.
Keywords: ANALISIS FINANCIER; INDICADORES FINANCIEROS; ESTADOS FINANCIEROS; ANALISIS VERTICAL